Preclinical profiles of SKB264, a novel anti-TROP2 antibody conjugated to topoisomerase inhibitor, demonstrated promising antitumor efficacy compared to IMMU-132 - Cheng, Yezhe; Yuan, Xiaoxi; Tian, Qiang; Huang, Xiuying; Chen, Yang; Pu, Yuzhi; Long, Hu; Xu, Mingyu; Ji, Yafei; Xie, Jia; Tan, Yuping; Zhao, Xi; et al. (Frontiers in Oncology, 2022)
Purpose: To improve intratumoral accumulation of antibody-drug conjugate (ADC) and minimize its off-target toxicity, SKB264, a novel anti-trophoblast antigen 2 (TROP2) ADC was developed using 2-methylsulfonyl pyrimidine as the linker to conjugate its payload (KL610023), a belotecan-derivative topoisomerase I inhibitor. The preclinical pharmacologic profiles of SKB264 were assessed in this study. Methods: In vitro and in vivo pharmacologic profiles of SKB264, including efficacy, pharmacokinetics-pharmacodynamics (PK-PD), safety and tissue distribution, were investigated using TROP2-positive cell lines, cell-derived xenograft (CDX), patient-derived xenograft (PDX) models and cynomolgus monkeys. Moreover, some profiles were compared with IMMU-132. Results: In vitro, SKB264 and SKB264 monoclonal antibody (mAb) had similar internalization abilities and binding affinities to TROP2. After cellular internalization, KL610023 was released and inhibited tumor cell survival. In vivo, SKB264 significantly inhibited tumor growth in a dose-dependent manner in both CDX and PDX models. After SKB264 administration, the serum or plasma concentration/exposure of SKB264 (conjugated ADC, number of payload units ≥1), total antibody (Tab, unconjugated and conjugated monoclonal antibody regardless of the number of the payload units) and KL610023 in cynomolgus monkeys increased proportionally with increasing dosage from 1 to 10 mg/kg. The linker stability of SKB264 was significantly enhanced as shown by prolonged payload half-life in vivo (SKB264 vs IMMU-132, 56.3 h vs 15.5 h). At the same dose, SKB264’s exposure in tumor tissue was 4.6-fold higher than that of IMMU-132. Conclusions: Compared with IMMU-132, the longer half-life of SKB264 had a stronger targeting effect and better anti-tumor activity, suggesting better therapeutic potential of SKB264 for treating TROP2-positive tumors.